Investigation of multiphase of multiphase flow instabilities and development of turbulence models for transient hydrodynamic slug flow in horizontal pipelines - Kouadjo, Bobo Claude (Cranfield University, 2023)
The knowledge of the slug flow is essential to the design and safety of hydrocarbon transportation in the pipelines systems of the petroleum industry. This thesis presents a theoretical and computational investigation of hydrodynamic slug flow in horizontal pipelines. As slug flow is part of multiphase flows, a literature review of multiphase models and their instabilities including the turbulent models involved. A focus on the anisotropic aspect of the prediction of turbulence has been considered by setting up a new turbulence model that will help us to solve this multiphase problem (hydrodynamic slug flow). A User-Defined Function based C code has been implemented to model the anisotropic turbulence for the new multiphase turbulence model created as a contribution to the knowledge. The Ansys Fluent computational fluid dynamics (CFD) software package has been used to set up the simulations with the aim of investigating the characteristics of slug flows such liquid holdup, pressure drops in different pipe sizes (diameter 16mm, 26mm and 50mm). The challenges including the three- dimensional simulations were carried out with both isotropic and anisotropic turbulent models to investigate the differences, similarities, and improvements. The isotropic simulations were validated with a journal paper (Deendarlianto et al., 2018). As a result, different flow patterns such as stratified Fig. (4-14.) and Fig. (4-15), pseudo slug Fig. (4-23.), slug Fig. (4-5) and Fig. (4-8) have been obtained. The analysis shows that at some time steps, numerical and experimental data values are very closed, showing a good validation. A comparative study has been performed to compare and assess the performance of isotropic and anisotropic simulations results for an industrially relevant engineering application. The validation shows a better result Fig. (4-43) compared to isotropic simulation.
Jenkins, Karl W. - Associate Supervisor
Keywords: Multiphase Anisotropic Turbulence; Computational Fluid Dynamics; Slug Flows; hydrocarbon transportation; petroleum; turbulent models